Investigating the economic burden of ALS in Greece: A cost-of-illness approach. Issue 1 (March 2015) - Athanasakis, Kostas; Kyriopoulos, Ilias-Ioannis; Sideris, Manthos; Rentzos, Michael; Evdokimidis, John; Kyriopoulos, John
Abstract: The present study aims to investigate the economic burden of ALS per patient in Greece. A sample of 33 patients who were monitored in Aeginition University Hospital in Athens, a reference centre for ALS in Greece, was used for the calculations. According to the findings of this study the total annual cost per ALS patient in Greece was €7450. The direct cost was estimated at €4305 (or 57.8% of the total cost), while the indirect cost was €3145 (or 42.2% of the total cost). Medications, professional home help and cost due to work absenteeism were the leading components of total cost. In general, the aforementioned amount is considered substantial, albeit lower than the corresponding amount of other countries.